Lightning performance analysis of a rooftop grid-connected solar photovoltaic without external lightning protection system - Nasir M.S.M.; Ab-Kadir M.Z.A.; Radzi M.A.M.; Izadi M.; Ahmad N.I.; Zaini N.H. (Public Library of Science, 2023)
amplitude modulation; Article; electric current; electric potential; energy resource; lightning; Malaysia; reliability; solar photovoltaic rooftop system; surge protection device; validation process; waveform; computer system; electrode; electromagnetism; hospital; human; power supply; reproducibility; Computer Systems; Electric Power Supplies; Electrodes; Electromagnetic Phenomena; Hospitals; Humans; Lightning; Malaysia; Reproducibility of Results